Changes in free fatty acid composition during storage of whole milk powder - Paez, Roxana (2006)
Changes in fat matter due to the microbial thermostable lipases are among the most significant deteriorations influencing the shelf life of whole milk powder. As a consequence, free fatty acids are produced, being the short-chain acids mainly responsible for the rancidity flavour. The aim of this work was to evaluate changes in different fatty acid concentrations during the storage of whole milk powder produced in two different seasons. Samples of whole milk powder produced in winter and summer and packed under inert atmosphere were used in the study. The samples were stored at 21°C and 40°C. Samples stored at 21°C were evaluated every 3 months, whereas samples stored at 40°C were evaluated monthly by free fatty acids profile and sensory analysis. Data were processed by principal component analysis and anova. Results showed that changes in the free fatty acids of milk powders were correlated with the season of manufacture. Temperature and storage time had little influence on that profile.